Evaluation of forming limit diagrams of stainless Steel AISI 304 and AISI 430 - da Rocha, Rafael Pandolfo; Riffel, Matheus Henrique; Schaeffer, Lirio (Desenvolvimento em Questão, 2023)
Current quality standards require standardized tests in order to employ metal sheets in deep drawing processes. These tests are conducted aiming to assess their degree of formability in order to ensure that these materials can be formed without any defects such as wrinkling, earing, or even localized rupture. To evaluate whether a piece can be stamped without failures, the forming limit curve (FLC) is used, which provides data on the deformations that materials can withstand under certain modes of plastic deformation during stamping processes. In summary, the behavior of the maximum and minimum principal deformations of a stamped component is compared with the material’s FLC: any combination located below the curve means deformations that the material can withstand, and consequently, those located above indicate its rupture. The objective of this article is to determine through experiments the FLCs of austenitic AISI 304 and ferritic AISI 430 stainless steels, using three different lubricants (Draw 58 GS, Neutron Super Corte 1123-21S, and Flash Stamp 140), in order to account for the influence of lubricants and, consequently, friction on the behavior of the forming limit curves.